Structural Extension to Logistic Regression Discriminative Parameter Learning of Belief Net Classifiers. - Greiner, Russell
Bayesian belief nets (BNs) are often used for classification tasks-typically to return the most likely class label for each specified instance. Many BN-learners, however, attempt to find the BN that maximizes a different objective function-viz., likelihood, rathen than classification accuracy-typically by first learning an appropriate graphical structure, then finding the parameters for that structure that maximize the likelihood of the data. As these parameters may not maximize the classification accuracy, "discriminative parameter learners" follow the alternative approach of seeking the parameters that maximize conditional likelihood (CL), over the distribution of instances the BN will have to classify. This paper first formally specifies this task, shows hot it extends standard logistic regression, and analyzes its inherent sample and computational complexity. We then present a general algorithm for this task, ELR, that applies to arbitrary BN structures and that works effectively even when given incomplete training data. Unfortunately, ELR is not guaranteed to find the parameters that optimize conditional likelihood; moreover, even the optimal-CL parameters need not have minimal classification error. This paper therefore presents empirical evidence that ELR produces effective classifiers, often superior to the ones produced by the standard "generative" algorithms, especially in common situations where the given BN-structure is incorrect.
Keywords: (Bayesian) belief nets; Logistic regression; Classification; PAC-learning.; Computational/sample complexity